Digital work in Eastern Europe: Overview of trends, outcomes and policy responses - Marijya Aleksynska (International Labour Organization (ILO), 2021)
This paper documents the emergence and growth of digital labour markets in Eastern Europe. It shows that the development of two types of digital work - online work through online labour platforms and offline work mediated by mobile apps - have a different history, root causes and dynamics. While both are enabled by digital technologies, each attracts a different worker profile and results in different outcomes for workers. The paper also reviews policy responses to digital work in three areas: bringing digital work under the scope of existing regulations; ensuring fair competition with workers in traditional forms of employment; and improving formalization and better tax compliance of digital workers. It concludes by discussing how low scope for organizing digital workers, poor law enforcement and proliferation of new modes of digital work remain key obstacles for effective regulation.
Keywords: 330; decent work; future of work; non-standard forms of employment; digital labour; conditions of employment; social dialogue; labour standards; gig economy; digital work; online labour markets; gig economy; labour platforms; work via apps